Russia and Western concepts of deterrence, normative power, and sanctions. Issue 3 (4th May 2021) - Veebel, Viljar
Abstract: The North Atlantic Treaty Organization (NATO), the European Union (EU), and the Russian Federation have invested their energy in convincing the opposing side about the legitimacy, importance, and even supremacy of their international political narratives. While the West is committed to value based international order, economic and political sanctions, and credible deterrence, Russia is pushing for a concept of a Eurasian center of power, a multipolar world order, and the importance of the Raison d' État . These two energetic monologues, however, have provided little dialogue or actual results in terms of cooperation or de-escalation. Can these competing concepts be simultaneously successful at all, or does one side need to fundamentally redesign its conceptual principles?